Peningkatan Kemampuan Berpikir Kritis Peserta Didik Melalui Model Pembelajaran Problem Based Learning pada Materi Kimia Hijau - Elyn Fadya Elyn Fadya; Mukhamad Nurhadi; Sri Lestari (FKIP University of Mataram, 2026)
Critical thinking skills are an important tool for achieving success in the 21st century. Students’ critical thinking skills need to be trained so that they are able to think in solving problems. Therefore, a learning model that can improve students’ critical thinking skills is needed, one of which is the implementation of the Problem-Based Learning (PBL) model. This study aimed to determine the improvement of students’ critical thinking skills through the PBL learning model in green chemistry material. The sample of this study consisted of 30 tenth-grade students at SMAN 16 Samarinda, who were selected using purposive sampling technique. This research was a descriptive quantitative study using a one-group pretest–posttest design. Data were collected through test techniques in the form of pre-tests and post-tests, and non-test techniques in the form of documentation, observation, and questionnaires. Data analysis was conducted using the N-Gain test and the Effect Size test, preceded by statistical tests. The results showed that there was an improvement in students’ critical thinking skills through the Problem-Based Learning model in green chemistry material. The average N-Gain for the three classes was 0,611, which was categorized as moderate. The average Effect Size for the three classes was 4,33, which was categorized as large. Based on the results of the data analysis, it can be concluded that there was an improvement in students’ critical thinking skills through the Problem-Based Learning (PBL) model in green chemistry material. Keywords: improvement, critical thinking skills, problem-based learning